RANCANG BANGUN APLIKASI TATA KELOLA DESA BERBASIS WEB MENGGUNAKAN METODE WATERFALL DI KANTOR DESA SEPUKUR - M. Julkarnain; Herfandi; Deri Afriliyansa (Jurnal Informatika Teknologi dan Sains, 2021)
This study research to design and build a web-based village governance application by using the Waterfall method at the Sepukur village office. This application development model enhances the previous system for later use by the Sepukur Village office. This system is designed and built using the PHP programming language with codeigneter framework and MySQL database. The software development method uses the waterfall method and qualitative for data collection methods. The test method is carried out through black-box testing, namely testing carried out, namely testing carried out based on functionality. In designing a web-Sepukur village governance application in Sepukur Village, it has several management, namely managing correspondence, population and letter archiving. This web-based village management application is expected to be able to assist the village government in providing mail services quickly and can minimize letter loss and damage.